Wall shear stress and its role in atherosclerosis - Zhou, Manli; Yu, Yunfeng; Chen, Ruiyi; Liu, Xingci; Hu, Yilei; Ma, Zhiyan; Gao, Lingwei; Jian, Weixiong; Wang, Liping (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerosis (AS) is the major form of cardiovascular disease and the leading cause of morbidity and mortality in countries around the world. Atherosclerosis combines the interactions of systemic risk factors, haemodynamic factors, and biological factors, in which biomechanical and biochemical cues strongly regulate the process of atherosclerosis. The development of atherosclerosis is directly related to hemodynamic disorders and is the most important parameter in the biomechanics of atherosclerosis. The complex blood flow in arteries forms rich WSS vectorial features, including the newly proposed WSS topological skeleton to identify and classify the WSS fixed points and manifolds in complex vascular geometries. The onset of plaque usually occurs in the low WSS area, and the plaque development alters the local WSS topography. low WSS promotes atherosclerosis, while high WSS prevents atherosclerosis. Upon further progression of plaques, high WSS is associated with the formation of vulnerable plaque phenotype. Different types of shear stress can lead to focal differences in plaque composition and to spatial variations in the susceptibility to plaque rupture, atherosclerosis progression and thrombus formation. WSS can potentially gain insight into the initial lesions of AS and the vulnerable phenotype that gradually develops over time. The characteristics of WSS are studied through computational fluid dynamics (CFD) modeling. With the continuous improvement of computer performance-cost ratio, WSS as one of the effective parameters for early diagnosis of atherosclerosis has become a reality and will be worth actively promoting in clinical practice. The research on the pathogenesis of atherosclerosis based on WSS is gradually an academic consensus. This article will comprehensively review the systemic risk factors, hemodynamics and biological factors involved in the formation of atherosclerosis, and combine the application of CFD in hemodynamics, focusing on the mechanism of WSS and the complex interactions between WSS and plaque biological factors. It is expected to lay a foundation for revealing the pathophysiological mechanisms related to abnormal WSS in the progression and transformation of human atherosclerotic plaques.